Post-hidatid biliary stenoses and their consequences - Perdomo, Roberto; López, Julio; Delbene, Roberto; Castro, Danilo; Santana, Carlos H; Bertolini, Carlos; Ruocco, Alvaro; Carbó, Alberto; Tiscornia, Eduardo; Gaudiano, Javier (Cirugía del Uruguay, 1985)
Development of the hypothesis that the opening or biliocystic fistule left by a hydatic cyst in the Jiliary tract when opened and partially evacuated, is equivalen! to a wound in same and, as in such wound, healing will be followed by total or partial stenosis of the duct in which it has been set.